Antiviral Activity of the Marine Haptophyta Diacronema lutheri - Eleonora Montuori; Annalisa Ambrosino; Gerardo Della Sala; Costanza Ragozzino; Gianluigi Franci; Carla Zannella; Anna De Filippis; Donatella de Pascale; Massimiliano Galdiero; Chiara Lauritano (Marine Drugs)
There are still several viral infections affecting a considerable number of the world’s population, causing thousands of deaths each year. There are no drugs available for most viral infections and for many not even a vaccine. The marine kingdom is characterized by a huge chemical diversity; however, there is currently on the market only one drug derived from the sea with antiviral properties, called Ara-A. In the current study, we used a solid phase extraction method (SPE) to obtain pre-purified fractions from Diacronema lutheri raw extracts. We tested both raw extracts and fractions against enveloped and non-enveloped viruses. Results showed an antiviral activity of fraction C of D. lutheri against the herpes simplex virus type 1 (HSV-1 strain SC16). Liquid chromatography coupled with untargeted high-resolution tandem mass spectrometry (LC-HRMS2) were employed to chart the metabolite distribution in all SPE fractions and pinpoint molecular families unique (or almost unique) to the bioactive fraction. Sulfoquinovosyl di- and monoacylglycerols (SQDGs and SQMGs) and di- and monogalactosyl monoacylglycerols (DGMGs and MGMGs) represent the largest groups of compounds in fraction C and they are likely responsible for the antiviral properties of this fraction.